1975
DOI: 10.1152/ajplegacy.1975.229.5.1403
|View full text |Cite
|
Sign up to set email alerts
|

Potassium transport in the distal tubule and collecting duct of the rat

Abstract: Because of recent conflicting results, micropuncture studies were performed to clarify the respective role of the distal convoluted tubule and collecting duct in the regulation of urinary potassium excretion. Five groups of Sprague-Dawley rats were studied: group I, hydropenia (n = 10); group II, Ringer loading (n = 7); group III, acute KC1 loading (n = 6); group IV, mannitol diuresis (n = 6); group V, KC1 infusion during mannitol diuresis (n = 7). Early and late distal tubules were identified with intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
1

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 0 publications
5
16
1
Order By: Relevance
“…Borenstein et al (1983) reported that injection of atrial extract into anesthetized rats increased total and medullary blood flow in the kidney. In the present study, the prolonged kaliuresis was accompanied by the diuresis, which suggests that urine flow into the distal tubule may have increased after the injection of a-hANP, since it has been shown that potassium secretion is increased when flow into the distal tubule is increased (Malnic et al 1966;Morgan and Berliner 1969;Kunau et al 1974; Khuri et al 1975;Reineck et al 1975;Diezi et al 1976). This increase in urine flow into the distal tubule could have been elicited by the dissipation of corticomedullary osmotic gradient by medullary washout.…”
Section: Resultssupporting
confidence: 58%
“…Borenstein et al (1983) reported that injection of atrial extract into anesthetized rats increased total and medullary blood flow in the kidney. In the present study, the prolonged kaliuresis was accompanied by the diuresis, which suggests that urine flow into the distal tubule may have increased after the injection of a-hANP, since it has been shown that potassium secretion is increased when flow into the distal tubule is increased (Malnic et al 1966;Morgan and Berliner 1969;Kunau et al 1974; Khuri et al 1975;Reineck et al 1975;Diezi et al 1976). This increase in urine flow into the distal tubule could have been elicited by the dissipation of corticomedullary osmotic gradient by medullary washout.…”
Section: Resultssupporting
confidence: 58%
“…Similar findings have also been described previously by Merlet-Benichou and de Rouffignac (20) in near-term fetal guinea pigs. These authors suggested that the increascd ability of thc fetal kidncy to cxcrctc morc potassium as gcstation advanced was a flow-dependent phenomenon as described in adult animals (10,24,38 ). However, in the present study there was no significant correlation between fetal urinary flow rate and fractional excretion of potassium (r = -0.18) suggesting that in chronically catheterized fetal lambs, urinary flow rate does not play an important role in the maturation process of potassium excretion.…”
Section: Discussioncontrasting
confidence: 53%
“…Beck et al (51) have reported that ACZ did not change fractional reabsorption of K in the proximal tubule. In addition it is generally accepted that the bulk of urinary K is derived from a distal secretory process (40,52,53) and that K secretion is dependent upon urinary flow rate, per se (54)(55)(56). Fig.…”
Section: Resultsmentioning
confidence: 99%